Antifungal activity of lactic acid bacteria from Pangasius catfish culture in the Mekong Delta, Vietnam - Quach Van Cao Thi; Tu Thanh Dung; Nguyen Bao Trung; Nguyen Phuong Thuy (Veterinary Integrative Sciences, 2024)
Fungi are one of the most common pathogens in aquaculture. The study was performed to isolate and select lactic acid bacteria (LAB) with antifungal activity. A total of 36 isolates of LAB were isolated from the intestines of Pangasianodon hypophthalmus, water and sludge, fermented vegetables, and “com me” in Vinh Long province of the Mekong Delta, Vietnam. The results revealed that the isolated LAB isolates were inhibitory against five species of fungi: Aspergillus sp., Fusarium sp., Achlya sp., Saprolegnia sp., and Mucor sp. In particular, isolate LN12 showed the highest activity against Aspergillus sp., Fusarium sp., Achlya sp., Saprolegnia sp., and Mucor sp. with inhibition diameters of 20 mm, 19.33 mm, 19.67 mm, 19.0 mm, and 20.33 mm, respectively. An investigation on the influence of culture conditions showed that all four bacterial isolates, LN5, LN12, LN23, and LN31, had the highest antifungal activity at a concentration of 108 CFU/ml after incubation for 48-60 hours, incubation temperature of 30–35oC, pH of 5.0–6.0 in the medium without the addition of NaCl. Four bacterial isolates, LN5, LN12, LN23, and LN31, were identified as Lactobacillus, and LN33 belonged to Pediococcus based on morphological and biochemical characteristics, and 16S-rRNA gene sequencing. The results show the potential application of LAB isolates in the prevention of fungal diseases in catfish.